2015
DOI: 10.1093/brain/awv095
|View full text |Cite
|
Sign up to set email alerts
|

Visual-spatial memory may be enhanced with theta burst deep brain stimulation of the fornix: a preliminary investigation with four cases

Abstract: Memory loss after brain injury can be a source of considerable morbidity, but there are presently few therapeutic options for restoring memory function. We have previously demonstrated that burst stimulation of the fornix is able to significantly improve memory in a rodent model of traumatic brain injury. The present study is a preliminary investigation with a small group of cases to explore whether theta burst stimulation of the fornix might improve memory in humans. Four individuals undergoing stereo-electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
79
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 28 publications
2
79
1
1
Order By: Relevance
“…Improvement in verbal memory was demonstrated with chronic hippocampal stimulation delivered in response to seizures and epileptiform activities using a responsive neurostimulation device (RNS) [7]. Studies with acute hippocampal stimulation have shown positive and negative effects on memory depending on stimulation frequencies (1–50 Hz versus > 100 Hz) and site of stimulation (hippocampal versus fornix stimulation) [8], [9], [10], [11]. Note that the stimulation in these studies did not induce a seizure, unlike our study.…”
Section: Discussioncontrasting
confidence: 50%
“…Improvement in verbal memory was demonstrated with chronic hippocampal stimulation delivered in response to seizures and epileptiform activities using a responsive neurostimulation device (RNS) [7]. Studies with acute hippocampal stimulation have shown positive and negative effects on memory depending on stimulation frequencies (1–50 Hz versus > 100 Hz) and site of stimulation (hippocampal versus fornix stimulation) [8], [9], [10], [11]. Note that the stimulation in these studies did not induce a seizure, unlike our study.…”
Section: Discussioncontrasting
confidence: 50%
“…We discuss six aDES studies on memory modulation which provide a useful framework for considering the varying effects of hippocampal stimulation on memory performance (Coleshill et al, 2004;Fell et al, 2013;Koubeissi, Kahriman, Syed, Miller, & Durand, 2013;Lacruz et al, 2010;Miller et al, 2015;Suthana et al, 2012). These studies all used depth electrodes targeting the hippocampus, parahippocampal cortex, or fornix.…”
mentioning
confidence: 99%
“…One approach is to use other patient populations—where electrodes are already implanted for established clinical reasons—to test effect of stimulation on cognitive parameters impaired in AD, specifically episodic memory or spatial navigation. Indeed, such an approach has been employed in neurosurgical epilepsy patients by Suthana et al [9] where stimulation was applied in the entorhinal area during encoding and by Miller et al [10] with stimulation applied at the posterior fornix. Another approach is to conduct smaller adaptive trials where several therapeutic variables can be systematically altered.…”
mentioning
confidence: 99%
“…These include stimulation protocols, as considerable variability can be seen even in the few memory trials conducted to date. For instance, Suthana et al [9] have used 50 HZ stimulation for 5 s on-off periods applied unilaterally, Miller et al [10] have used unilateral theta burst stimulation over longer period of times (20 min and more), and Laxton et al [2] have used continuous bilateral 130 Hz stimulation. At the same time, further animal experiments enabling more precise well-defined manipulation of neuronal circuits in disease models should be employed.…”
mentioning
confidence: 99%